Mortality Rate of Fish Seeds (Labeo rohita) During Traditional Transportation System in the Northwest Bangladesh (Journal of Scientific Research, 2013)
This investigation deals with the mortality rate of fish seeds (Labeo rohita) during traditional transportation system; to evaluate the effects of loading density with time scale under different water medium; temperature effect with relation to fry size and oxygen consumption; and the effect of saline water bath before transportation. Mortality rates were significantly increased with time scale and loading density under different water medium. Higher mortality was observed at 400 g L-1 loading density (river water 82%, pond water 70% and tubewell water 67.5%) than at 200 g L-1 and 300 g L-1 loading density after 24h. Oxygen consumption rate increased signi?cantly with increasing temperature and decreased significantly with increasing fry body weight. Therefore, mortality rate could decrease (22%) if fish fry are bathed in saline water before journey and tubewell water can be use as a medium for long distance transportation.Keywords: Mortality; Fish seeds; Oxygen consumption; Transportation.© 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.doi: http://dx.doi.org/10.3329/jsr.v5i2.10572         J. Sci. Res. 5 (2), 383-392 (2013)